2020
DOI: 10.4049/jimmunol.1901456
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish GSDMEb Cleavage-Gated Pyroptosis Drives Septic Acute Kidney Injury In Vivo

Abstract: The bacteria LPS is one of the leading endotoxins responsible for sepsis; its sensing pathway–induced pyroptosis plays an important role in innate immunity. However, excessive pyroptosis might cause immunological diseases, even multiple organ failure and death by undefined mechanisms. Given that the development of acute kidney injury (AKI) in patients with sepsis causes significant morbidity and mortality, the mechanism of pyroptosis in regulating septic AKI remains unknown. In this study, we establish a zebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 56 publications
3
50
0
Order By: Relevance
“…In vivo, the Gsdme-derived inhibitor, Ac-DMLD-CMK, alleviated deterioration of kidney function, attenuated renal tubular epithelial cell injury, reduced inflammatory cytokine secretion, and inhibited caspase 3-GSDME signaling induced by cisplatin. Similarly, a previous study reported that GSDMEb knockout-or GSDMEb-derived inhibitor Ac-FEID-CMK-treated zebrafish exhibited reduced proximal renal tubule structure injury compared to the control, indicating that GSDMEb plays an essential role in proximal tubular cell pyroptosismediated AKI in zebrafish 46 . In fact, in addition to the kidney, GSDME also plays an important role in other organs and diseases, however, most of the current studies on GSDME focus on tumors 14 .…”
Section: Discussionsupporting
confidence: 55%
“…In vivo, the Gsdme-derived inhibitor, Ac-DMLD-CMK, alleviated deterioration of kidney function, attenuated renal tubular epithelial cell injury, reduced inflammatory cytokine secretion, and inhibited caspase 3-GSDME signaling induced by cisplatin. Similarly, a previous study reported that GSDMEb knockout-or GSDMEb-derived inhibitor Ac-FEID-CMK-treated zebrafish exhibited reduced proximal renal tubule structure injury compared to the control, indicating that GSDMEb plays an essential role in proximal tubular cell pyroptosismediated AKI in zebrafish 46 . In fact, in addition to the kidney, GSDME also plays an important role in other organs and diseases, however, most of the current studies on GSDME focus on tumors 14 .…”
Section: Discussionsupporting
confidence: 55%
“…the caspy2-GSDMEb signaling pathway was essential in LPSinduced fatal renal tubular injury caused by septic shock, and the specific GSDMEB inhibitor Ac-FEID-CMK could reduce the incidence of septic AKI and zebrafish mortality (55). These results highlight potential therapeutic targets of septic AKI.…”
Section: Pyroptosis Mediates Sepsis-related Organ Damagementioning
confidence: 82%
“…It is likely that the contrast agents damage the membrane of epithelial cells, entering into the cells to activate caspase-4/5/11, to cleave GSDMD, and to initiate pyroptosis [ 61 ]. An up-to-date study found that pyroptosis mediated by the caspase-11/GSDMD signaling pathway not only affected the release of cytokines but also determined the severity of AKI following septic shock [ 62 ]. These results suggest a close correlation between the pathogenesis of AKI and the caspase-4/5/11-mediated atypical pathway in pyroptosis.…”
Section: Association Between Pyroptosis and Kidney Diseasementioning
confidence: 99%